Analisis Perbandingan Suku Bunga Berjangka Pada Koperasi Simpan Pinjam dan Bank Umum (Studi Kasus Pada KSP Neo Esens Indonesia) - Gurhanawan G; Indri Saraswati; Dinda Ayu Lestari; Devi Handayani; Wanda Kirana (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Savings and Loans Cooperative is a non-bank financial institution, whose products are similar to those of a bank, namely saving funds in the form of savings and channeling them in the form of credit (loans), but their distribution is limited to members of the cooperative and the surrounding community. The object of this study is KSP Neo Esens Indonesia, one of the products of which is a term savings (deposit). Interest rates applied are higher than commercial banks whose goal is to attract cooperative members and the public to invest their funds in cooperatives which will have an impact on cooperative profits in order to achieve member welfare. The research method used is the comparative method, namely comparing the condition of one or more variables in two or more different samples, or two different times.